1998
DOI: 10.1086/300271
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Irradiance Calibration in the Infrared. VIII. 5–14 Micron Spectroscopy of the Asteroids Ceres, Vesta, and Pallas

Abstract: We describe our e †orts to seek "" closure ÏÏ in our infrared absolute calibration scheme by comparing spectra of asteroids, absolutely calibrated through reference stars, with "" standard thermal models ÏÏ and "" thermophysical models ÏÏ for these bodies. Our use of continuous 5È14 km airborne spectra provides complete sampling of the rise to, and peak, of the infrared spectral energy distribution and constrains these models. Such models currently support the absolute calibration of the Infrared Space Observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…If IDPs are dominated by silicate-type particles of the size distribution with an enhancement of submicron particles, such as the lunar microcrater distribution (Grün et al, 1985), they may show band features in the 10 μm region (Reach et al, 1996b). A recent study of asteroids also suggests the presence of band features in the 10 μm region of the spectrum of Ceres (Cohen et al, 1998). Therefore, the presence of features in the 10 μm region of the zodiacal emission is not unexpected and the near-infrared zodiacal light and the mid-infrared zodiacal emission may be interpreted consistently in terms of the silicate-type IDPs.…”
Section: Discussionmentioning
confidence: 73%
“…If IDPs are dominated by silicate-type particles of the size distribution with an enhancement of submicron particles, such as the lunar microcrater distribution (Grün et al, 1985), they may show band features in the 10 μm region (Reach et al, 1996b). A recent study of asteroids also suggests the presence of band features in the 10 μm region of the spectrum of Ceres (Cohen et al, 1998). Therefore, the presence of features in the 10 μm region of the zodiacal emission is not unexpected and the near-infrared zodiacal light and the mid-infrared zodiacal emission may be interpreted consistently in terms of the silicate-type IDPs.…”
Section: Discussionmentioning
confidence: 73%
“…At shorter wavelength, between 8 and 11 µm, broadband silicate features have been seen (Cohen et al 1998;Dotto et al 2000). Heras et al (2000) report mid-IR emission signatures on Vesta, tentatively identified with olivine and pyroxene silicate groups.…”
Section: Asteroid Ir Observational Aspectsmentioning
confidence: 96%
“…The mid-infrared spectral region is also proving to be diagnostic of the surface composition of primitive asteroids, and in ways complementary to the shorter wavelengths (e.g., Cohen et al 1998;Müller & Blommaert 2004;Lim et al 2005;Emery et al 2006;Campins et al 2007). The three published midinfrared spectra, from 5 to 38 μm of Trojan asteroids (Emery et al 2006) exhibit clear emissivity features from which the compositional and physical properties can be inferred.…”
Section: Introductionmentioning
confidence: 99%